Additions to Philippine Slender Skinks of the Brachymeles bonitae Complex (Reptilia: Squamata: Scincidae) II: a new species from the northern Philippines - Siler, Cameron D.; Davis, Drew R.; Freitas, Elyse S.; Huron, Nicholas A.; Geheber, Aaron D.; Watters, Jessa L.; Penrod, Michelle L.; Papeș, Monica; Amrein, Andrew; Anwar, Alyssa; Cooper, Dontae; Hein, Tucker; et al. (Zootaxa, 2016)
We describe a new digitless scincid lizard of the genus Brachymeles from northern Luzon and Camiguin Norte islands in the Philippines. This species belongs to the Brachymeles bonitae Complex, and both molecular and morphological data confirm that this species is distinct from all other congeners. Formerly considered to be a single widespread species, this group of species has been the focus of recent systematic reviews. Here we describe a new species in the B. bonitae Complex, recognized currently to constitute five species. Brachymeles ilocandia sp. nov. is the second digitless and the seventeenth non-pentadactyl species in genus. The description of this species brings the total number of species in the genus to 40, and provides new insight into unique distribution patterns of species of the northern Philippines.